Immunohistochemical detection of parainfluenza type 3 virus antigens in paraffin sections of pneumonic caprine lungs - Yener, Z; Saglam, YS; Timurkaan, N; Ilhan, F (Blackwell Publishing, 2005)
Pneumonia is a leading cause of loss to ruminants throughout the world. Parainfluenza type-3 virus (PI-3) is one of the most important respiratory pathogens of bovine and ovine. In this study, prevalence of PI-3 virus infection as causative agent of pneumonia in goats was investigated. For this purpose, a total of 1505 goat lungs slaughtered in Bitlis and Van slaughterhouses were grossly examined and pneumonia was detected in 74 cases (4.91%). Lesions were more frequently encountered in anteroventral lobes than caudal lobes. With the exception of verminous pneumonia observed in 32 cases, immunohistochemical examinations were performed on 42 pneumonic lungs. Formalin-fixed and paraffin-embedded lung tissue samples were immunohistochemically stained by the avidin-biotin-peroxidase complex procedure using polyclonal antibodies to detect PI-3 viral antigens. The presence of PI-3 viral antigens was detected in 28 (66.6%) of 42 pneumonic lungs. Viral antigens were found most frequently in the cytoplasm of bronchiolar epithelial cells, type II pneumocytes, and less frequently in the epithelial cells of bronchial glands, syncytial cells, alveolar macrophages, and lymphocytes and plasma cells. In conclusion, it was found that there was a close relationship between the pneumonia in goats and the presence of PI-3 viral antigens. Incidence of PI-3 virus in pneumonic lungs of goats was detected to be very high in the present study performed in the region of Bitlis and Van, Turkey.
Keywords: Respiratory Syncytial Virus; Bovine Viral Diarrhea; Pasteurella-Haemolytica; Antibodies; Infections; Lambs; Goats; Sheep; Para-Influenza-3; Herpesvirus-1